Integrated Stock Information System on Smartphone Stores - sukadi sukadi; Candra Budi Susila (Universitas Darussalam Gontor, 2022)
AbstractThis research is motivated by the increasing number of smartphone shops nowadays, where there are many shops where if a buyer asks for goods and it happens that the stock of goods in the store is empty, the seller will ask other stores directly for stock, so it is less effective in terms of time and prospects. buyers will wait a long time. Therefore, the purpose of this study is to create a prototype system to integrate stock in smartphone stores where stores that are integrated with the system can see each other's stock information from other stores in the system, so that it is expected to speed up or help sellers get information on which store which are still in stock. The methodology used in this research is literature study, observation, interviews, and software development using the waterfall method. This research produced a prototype of an integrated inventory integration information system at a smartphone store which also has a function for processing purchasing and sales data and more importantly a search menu for information on the availability of goods at other stores which if implemented properly will make it easier and faster for shop owners in the search for information on the availability of goods in other stores. The results of this research can be developed into a smartphone marketplace and its accessories in accordance with technological developments.Keywords: stock inventory integration, information system, smartphone shop AbstrakPenelitian ini dilatarbelakangi oleh semakin banyaknya toko smartphone saat ini, dimana banyak toko yang apabila ada pembeli yang menanyakan barang dan kebetulan stok barang di toko tersebut kosong maka penjual akan menanyakan stok barang ke toko lain secara langsung, sehingga kurang efektif dari sisi waktu dan juga calon pembeli akan menunggu lama. Oleh karena itu tujuan dari penelitian ini adalah membuat sebuah prototype system untuk mengintegrasikan stok barang pada toko smartphone dimana toko yang terintegrasi dengan sistem tersebut dapat saling melihat informasi stok barang dari toko lain di sistem tersebut, sehingga diharapkan dapat mempercepat atau membantu penjual mendapatkan informasi toko mana yang stok barangnya masih ada. Metodologi yang digunakan dalam penelitin ini adalah studi literatur, observasi, wawancara, dan pembuatan perangkat lunak menggunakan metode waterfall. Penelitian ini menghasilkan sebuah prototipe sistem informasi integrasi stok barang terpadu pada toko smartphone yang juga mempunyai fungsi untuk pengolahan data pembelian dan penjualan serta yang lebih utama adalah menu pencarian informasi ketersediaan barang di toko lain, yang jika diterapkan dengan baik maka akan mempermudah dan mempercepat para pemilik toko dalam pencarian informasi ketersediaan barang di toko lain. Hasil dari penelitian ini bisa dikembangkan menjadi sebuah marketplace smartphone dan kelengkapannya yang sesuai dengan perkembangan teknologi.Kata kunci : integrasi stok barang, system informasi toko smartphone